Comparison between Mesenchymal Stem Cells obtained from Bone Marrow, Adipose Tissue and Wharton Gelatin according to the ISCT Criteria - Parra Barrera, A.; Murúa Beltran García, X.; Calzada Mendoza, C. C.; Cáceres Cortés, J. R.; Reyes Maldonado, E.; Gutiérrez Iglesias, G. (Revista Mexicana de Ingenieria Biomedica, 2017)
Mesenchymal stem cells (MSC) represent a heterogeneous population with the capacity to self-renew and differentiate into different cell types. At the middle of the last century these cells initially were described in bone marrow (BM), thence this tissue has become the gold standard for obtaining and characterization of MSC. It is known that these cells are housed in specific areas called niches distributed throughout all body, where they contribute to tissue regeneration processes of self-tissue were they are located. However, finding an alternative source of CTM with the same characteristics that have showed in MO, but its obtention no represent a risk since the donor is essential to their use for therapeutic purposes. In this study we isolated mesenchymal stem cells from bone marrow, adipose tissue and Wharton’s jelly and they were compared in their characteristics in according to the standards of the International Society for Cellular Therapy (ISCT). The results showed that the morphology as well as adipogenic and osteogenic differentiation and also the expression of surface antigens (CD90, CD73, and CD105) from all tissues accomplished the standards, although Wharton’s jelly represented the best option.